2018
DOI: 10.3389/fcimb.2018.00260
|View full text |Cite
|
Sign up to set email alerts
|

Type VI Secretion Systems Present New Insights on Pathogenic Yersinia

Abstract: The type VI secretion system (T6SS) is a versatile secretion system widely distributed in Gram-negative bacteria that delivers multiple effector proteins into either prokaryotic or eukaryotic cells, or into the extracellular milieu. T6SS participates in various physiological processes including bacterial competition, host infection, and stress response. Three pathogenic Yersinia species, namely Yersinia pestis, Yersinia pseudotuberculosis, and Yersinia enterocolitica, possess different copies of T6SSs with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 88 publications
1
24
0
1
Order By: Relevance
“…77 These core-component proteins are categorized into different subunits: the membrane complex (TssJLM), the baseplate complex (TssAEFGK), needle sheath complex (TssBC), sheath recycling ATPase (TssH), and the injection apparatus (Hcp, VgrG). 78 In the present study we found 12 such core-component proteins (TssABC, Hcp1, TssFGH, VgrG, TssJKLM) and two additional auxiliary component proteins (TagH and TagF) ( Table 2). Interestingly, most of these proteins found to be in the cytoplasmic region which suggests that these cytoplasm proteins can be further investigated for enhanced understanding of secreted protein transport during the pathogenesis.…”
Section: Analysis Of Type VI Secretion System Proteinssupporting
confidence: 53%
“…77 These core-component proteins are categorized into different subunits: the membrane complex (TssJLM), the baseplate complex (TssAEFGK), needle sheath complex (TssBC), sheath recycling ATPase (TssH), and the injection apparatus (Hcp, VgrG). 78 In the present study we found 12 such core-component proteins (TssABC, Hcp1, TssFGH, VgrG, TssJKLM) and two additional auxiliary component proteins (TagH and TagF) ( Table 2). Interestingly, most of these proteins found to be in the cytoplasmic region which suggests that these cytoplasm proteins can be further investigated for enhanced understanding of secreted protein transport during the pathogenesis.…”
Section: Analysis Of Type VI Secretion System Proteinssupporting
confidence: 53%
“…Thus, many T6SS-encoding bacteria tightly regulate their T6SS at transcriptional, posttranscriptional, and/or posttranslational levels (26,27). The complex regulatory networks governing T6SS activity enable bacteria to respond according to environmental signals, including: temperature, pH, cation/ nutrient availability, osmolarity, and membrane perturbation (26,(28)(29)(30)(31)(32)(33)(34)(35)(36). For instance, the antibacterial T6SS of Pseudomonas aeruginosa (HSI-I), regarded as a defensive T6SS, remains silenced unless P. aeruginosa perceives an attack from a competing bacterium (37).…”
mentioning
confidence: 99%
“…intermedia and Y. rohdei [64]. Various ABC transporters and a type-I fimbrial operon (D5F51_RS15015–D5F51_RS15045) were not present in Y.…”
Section: Resultsmentioning
confidence: 99%